Grafología forense: llave de ingreso al inconsciente criminal (2018)
This paper accounts for the importance that graphology has in the personnel processes from the study of the criminal profile. From the theoretical construct, the theory of descriptive and emotional graphology of Mauricio Xandró, Max Pulver and Augusto Vels are approached, which affirm that graphology is a technique that allows to identify emotional states, personality types, personality inclinations and this is used to determine if the person’s profile are adjusted to the needs of the organization, thus favoring the optimization of resources. Methodologically, it is an explanatory descriptive study of a documentary nature, since the main studies that exist in terms of graphology exist in the academy, mainly based on the acceptance of the documentary records as an instrument for the collection and analysis of information. As a conclusion, it was obtained that the forensic graphology allows to identify the concordance that exists between the profile, the behavior of the interviewee, the needs of the organization and the personality traits shown by the graphs inscribed by the interviewee. Besides that, it allows to design a supposed profile of the interviewee where the inclination of the psychic apparatus for the perpetration of an economic crime can be traced.